STUDY OF CULTURAL EDUCATION CURRICULUM EFFECTIVENESS IN NORTH SUMATRA - Harianto II; Zulfitri Zulfitri; Teguh Satria Amin (Jurnal Scientia, 2021)
This research was conducted to produce a teaching chart on art and culture which contains local content as the implementation of K13 for all schools in North Sumatra. This research was also conducted to reveal the side of cultural validation as well as the practicalization and effectiveness of arts and cultural education curricula that have local content such as Malay and Batak culture. The arts and culture education curriculum is one of the concerns of local government agencies to create validation in the cultural sector. There are several achievements in terms of learning validation which are in the valid and also practical categories. This of course shows the ability of users' interest, especially school children, in the teaching and learning process in the art and cultural education category. This research was conducted to improve the skills and attitudes of students regarding learning in the arts and culture category and to improve their abilities in the local cultural sector.